PELAKSANAAN TIME BUDGET PRESSURE DAN TURNOVER INTENTION TERHADAP PERILAKU DISFUNGSIONAL SERTA DAMPAKNYA TERHADAP KUALITAS AUDIT (SURVEI PADA AUDITOR EKSTERNAL PADA KANTOR AKUNTAN PUBLIK DI BANDUNG) - Mulyadi (LPPM POLITEKNIK LP3I BANDUNG, 2016)
ABSTRACT : This research tried to explain phenomenon of dysfunctional behavior personal auditor who work in Public Accounting Firms. It’s based on phenomenon which explanation that generally senior auditor who work in Public Accounting Firms have high level dysfunctional behavior. On based that, researcher estimation that the factors influence of dysfunctional behavior is time budget pressure and turnover intention have felt auditors. This research using multiple linear regression analyzes. Populations in this research is 78 senior auditors who work in Public Accounting Firms, from 78 senior auditors who become sample is 30 senior auditors.The result of this research showed that time budget pressure and turnover intention simultaneously have positive influence but not significant to dysfunctionl behavior with 3,3%. While partially, time budget pressure hasn’t significant influence with + 14,8%, and turnover intention hasn’t significant influence with + 24,9%. And than this research showed that dysfunctional behavior has negative influence but not significant to audit quality with 0,5 %.